Discovering Ngayaq Sasak Custom At Selaparang, Lombok - Muhhammad Husni Thamrin; Taufiq Kurniawan; Rabiatul Adawiyah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Ngayak Sasak is a form of old poetry used to express ideas, feelings, educational, and entertainment media. The purpose of this research is to gain concrete description about the forms of ngayak and its educational values. Based on the above explanation, in this research, the researcher tries to take the analysis of educational values and form of ngayak at Selaparang, Lombok, as the title of this thesis. The researcher uses the documentation technique and interview technique to collect the data by applying a direct question to the informants. The interview technique is used by the researcher to get the data that can be used as references in understanding Kayak. The research results are as follows: (1) Ngayak has close relationship with educational values, and it has high potential in society life because it contains a good suggestion and guidance for doing good deeds in our daily life. (2) For the societies, especially Selaparing society, it is hoped that the result of this study can be utilized as a guidance in investigating the values and norms contained in Ngayak Sasak.